Efeito de entomopatógenos e extratos vegetais sobre Apis mellifera L. (Hymenoptera: Apidae) - Silva, Rita Tatiane Leão da (2014)
Information on the effects of plant extracts and entomopathogens on non-target organisms such as pollinators, especially bees Apis mellifera L. (Hymenoptera: Apidae) are scarce. In this sense, the present work aimed to evaluate the effect of entomopathogenic microorganisms and plant extracts on A. mellifera. For this, the entomopathogenic Metarhizium anisopliae (Metarril® WP), Beauveria bassiana (Boveril® WP) and Bacillus thuringiensies subspecies Kurstaki (Thuricide® WP) and plant extracts of Romã (Punica granatum L.), Chapéu-de-couro (Echinodorus grandiflorus), Manjerona (Origanum majorana L.), Camomila (Matricaria recutita L.) were evaluated on the workers of A. mellifera in four different forms of application: 1 - direct spray of treatments on the worker bees; 2- contact in a glass surface sprayed with the treatments; 3- contact with soybean leaves immersed in the solution treatments and 4- mixing the treatments in a paste Candi pure. For the respective controls it has been used sterile distilled water and paste Candi pure. Each treatment consisted of five replicates, with 20 bees per replication, and these were placed in Gerboxes and later in a climate chamber type B.O.D. (27 ± 2 °C, U.R. 60% ± 10%, photoperiod of 12 h). The mortality / survival of the workers were assessed from one hour to 240 hours, and the data submitted to the Bayesian procedure. The workers bee killed by the ingestion of contaminated Candi paste were separated and randomly selected for the withdrawal of the midgut (ventricle) and subsequent histological analysis. The same quality and quantity have been assessed. The products Boveril®, Metarril® and Thuricide® and the plant extract of Manjerona, Camomila, Romã e Chapéu-de-couro have decreased the survival of A. mellifera workers. It has been found that the product Boveril® and the plant extract of Manjerona have reduced the survival of A. mellifera workers in all bioassays performed. The treatments with the biological commercial products Boveril® and Thuricide® caused morphological changes in the midgut of A. mellifera, when they were fed with Candi paste incorporated to these products.The plant extracts of Manjerona and Romã caused morphological changes, reducing the length of the midgut cells of A. mellifera, but without causing morphological changes. These results provide important information for the management of insect pests in order to conserve pollinator’s agents.